2016
DOI: 10.4103/0971-5916.182625
|View full text |Cite
|
Sign up to set email alerts
|

A study on pre-XDR & XDR tuberculosis & their prevalent genotypes in clinical isolates of Mycobacterium tuberculosis in north India

Abstract: Background & objectives:Pre-extensively drug resistant (pre-XDR) and extensively drug resistant tuberculosis (XDR-TB) have been areas of growing concern, and are posing threat to global efforts of TB control. The present study was planned to study the presence of pre-XDR and XDR Mycobacterium tuberculosis and their genotypes in clinical isolates obtained from previously treated cases of pulmonary TB.Methods:A total of 219 isolates obtained from previously treated cases of pulmonary TB were subjected to first-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…The reason for this was not clear from the data we had and a study with a significantly higher number of isolates would be able to explain the causality of this. In all, OFX resistance was higher in all regions studied, which was in line with previous studies 5 25 26 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The reason for this was not clear from the data we had and a study with a significantly higher number of isolates would be able to explain the causality of this. In all, OFX resistance was higher in all regions studied, which was in line with previous studies 5 25 26 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed a predominance of Beijing/CAS and EAI genotypes and an association between MDR and OFX resistance-conferring mutations and the Beijing genotype. A study from north India also observed Beijing as dominant genotype along with CAS_Delhi among OFX-resistant MDR-TB isolates 5 . While correlating the association of gyrA mutations in various lineages another study from north India found that the association of Beijing isolates was significantly high ( P =0.0006) with gyrA gene mutations 27 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The molecular epidemiology methods has been proven playing an important role in TB control and study 4 , 5 . Among these, spoligotyping has been considered as a powerful tool to differentiate M .…”
Section: Introductionmentioning
confidence: 99%
“…PreXDR-TB is defined as MDR-TB with resistance to either an FQ or a second line injectable (SLI), but not both [ 3 ]. The burden of pre-XDR-TB is considerable and represents a threat to MDR-TB control [ 4 , 5 ]. The World Health Organization (WHO) estimated 484 000 incident cases of MDR/RR-TB (MDR or rifampicin-resistant TB) in 2018 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%